Peningkatan Kepercayaan Diri Remaja Melalui Pelatihan Public speaking di SMPN 33 Makassar - Manda, Darman; Rahman, Abdul; Maya Kasmita; Sopia Rukmana, Novayanti; Darmayanti, Dyan Paramitha (Lembaga Dongan Dosen, 2023)
This community service aims to increase students' confidence and train their soft skills, namely public speaking. Through this PKM, it is hoped that it can be useful for students of SMPN 33 Makassar. The stages in this training are explaining materials that are closely related to public speaking, besides that the speaker will also explain the importance of communication in building relationships, and make students feel more confident. Public speaking does not only help students in increasing their self-confidence or just training soft skills but with the public speaking training conducted will help students improve their communication skills that can be used in forming relationships or communication networks, even expected in this training will also help the school to find talents that exist in students in the field of public speaking such as presenters or Master Of Ceremony (MC).